2008
DOI: 10.4324/9780203881804.pt6
|View full text |Cite
|
Sign up to set email alerts
|

Tourism Segmentation by Consumer-Based Variables

Abstract: The basis for successful marketing is to understand and satisfy consumer needs. Sometimes it is even possible to satisfy one individual customer's needs. In the tourism industry an individually customized tourism experience can be developed, but the market for such high-end tourism products is small. This does not, however, mean that the only alternative is to appeal to the mass market. The intermediate solution is to understand which groups of tourists have similar needs and develop tourism products that matc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…It was found that some tourists' motives differed between nationalities and places visited. Dolnicar and Kemp (2009), have expressed that in the tourism industry it is very important to understand which groups of tourists have similar needs and then to develop tourism products that meet particular groups' needs. It is interesting to note the methodological approaches used in the research reported here.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It was found that some tourists' motives differed between nationalities and places visited. Dolnicar and Kemp (2009), have expressed that in the tourism industry it is very important to understand which groups of tourists have similar needs and then to develop tourism products that meet particular groups' needs. It is interesting to note the methodological approaches used in the research reported here.…”
Section: Literature Reviewmentioning
confidence: 99%
“…International marketing research and practice has utilised cultural distinctions to understand consumer behaviour, and national-border segmentation bases have been used to better target specific consumer groups (Dolnicar and Kemp, 2009; Hassan and Katsanis, 1994; Helsen et al, 1993). Initially, benefits of national border’s segmentation might seem evident: there is little or no coordination of tourism marketing activities necessary between European countries (Yip, 1995).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the field of tourism research, there is evidence that studies still support the argument that national cultures form a distinctive base for distinguishing travel behaviour, and researchers agree that those geographical segmentations are still frequently applied (Dolnicar and Kemp, 2009; Moscardo et al, 2000; Tkaczynski et al, 2009). According to Pearce (2005: 133), most tourism research argues for diverging and heterogeneous cultures: ‘An implicit conceptual approach underlies much of the international market segmentation research in tourism.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the enormous body of research on tourism motivation and satisfaction regarding the Chinese market, research on marketing segments that consider a priori segmentation has not been conducted yet. The basis for successful marketing segmentation is to understand and satisfy the differences in consumer needs through different variables (Dolnicar & Kemp, 2009). An a priori segmentation leads to the identification of different groups of tourists according to prior knowledge, it has been used widely in tourism research (Dolnicar, 2004a(Dolnicar, , 2004bWedel & Kamakura, 2012).…”
Section: Introductionmentioning
confidence: 99%